Who's declining the “free lunch”? New evidence from the uptake of public child dental benefits - Ha Trong Nguyen; Huong Thu Le; Luke B. Connelly (Institute for Social Science Research, The University of Queensland, 2019)
Recent economic literature has advanced the notion that cognitive biases and behavioural barriers may be important influencers of uptake decisions in respect of public programs that are designed to help disadvantaged people. This paper provides the first evidence on the determinants of uptake of two recent public dental benefit programs for Australian children and adolescents from disadvantaged families. Using longitudinal data from a nationally representative survey linked to administrative data with accurate information on eligibility and uptake, we find that only a third of all eligible families actually claim their benefits. These actual uptake rates are about half of the targeted access rates that were announced for them. We provide new and robust evidence consistent with the idea that cognitive biases and behavioural factors are barriers to uptake. For instance, mothers with worse mental health or riskier lifestyles are much less likely to claim the available benefits for their children. These barriers to uptake are particularly large in magnitude: together they reduce the uptake rate by up to 10 percentage points (or 36%). We also find some indicative evidence that a lack of information is a barrier to uptake. The results are robust to a wide range of sensitivity checks, including controlling for possible endogenous sample selection.
https://www.lifecoursecentre.org.au/wp-content/uploads/2019/12/Nguyen_et_al_2019.pdf
Keywords: D91; H51; I12; I18; I38; 330; Government Programs; Impact Evaluation; Dental Health; Provision and Effects of Welfare Programs; Australia; Uptake; Take-up